Links among Quality, Satisfaction, Value, and Repurchase Intention in Gated Communities: Case from Kurdistan Region of Iraq - Zrian Ibrahim; Khayal Mahsum Faraj (Eurasian Journal of Management & Social Sciences)
The aim of this research was to elaborate the impact of product quality, service quality, customer satisfaction, and perceived value on the repurchase intentions of the residents in a gated community. We have collected data from the residents in various gated communities. Collected data was analyzed via structural equations modeling. The results reveal that product quality is a stronger influencer on the customer satisfaction than the service quality. Secondly, it was observed that product quality had significant impact on the perceived value while service quality was mediated on the perceived value via customer satisfaction. Lastly, it was observed that perceived value was very important determinant of repurchasing intentions of residents at a gated community and it was affected by customer satisfaction strongly. Service and product quality explained 56% of the variance on the customer satisfaction while they have explained 76% of the variance on perceived value and 65% of the variance on the repurchase intention.